Delta-8-THC: Delta-9-THC's nicer younger sibling? - Jessica S. Kruger; Daniel J. Kruger (BMC, 2022)
Abstract Background Products containing delta-8-THC became widely available in most of the USA following the 2018 Farm Bill and by late 2020 were core products of hemp processing companies, especially where delta-9-THC use remained illegal or required medical authorization. Research on experiences with delta-8-THC is scarce, some state governments have prohibited it because of this lack of knowledge. Objective We conducted an exploratory study addressing a broad range of issues regarding delta-8-THC to inform policy discussions and provide directions for future systematic research. Methods We developed an online survey for delta-8-THC consumers, including qualities of delta-8-THC experiences, comparisons with delta-9-THC, and open-ended feedback. The survey included quantitative and qualitative aspects to provide a rich description and content for future hypothesis testing. Invitations to participate were distributed by a manufacturer of delta-8-THC products via social media accounts, email contact list, and the Delta8 Reddit.com discussion board. Participants (N = 521) mostly identified as White/European American (90%) and male (57%). Pairwise t tests compared delta-8-THC effect rating items; one-sample t tests examined responses to delta-9-THC comparison items. Results Most delta-8-THC users experienced a lot or a great deal of relaxation (71%); euphoria (68%) and pain relief (55%); a moderate amount or a lot of cognitive distortions such as difficulty concentrating (81%), difficulties with short-term memory (80%), and alerted sense of time (74%); and did not experience anxiety (74%) or paranoia (83%). Participants generally compared delta-8-THC favorably with both delta-9-THC and pharmaceutical drugs, with most participants reporting substitution for delta-9-THC (57%) and pharmaceutical drugs (59%). Participant concerns regarding delta-8-THC were generally focused on continued legal access. Conclusions Delta-8-THC may provide much of the experiential benefits of delta-9-THC with lesser adverse effects. Future systematic research is needed to confirm participant reports, although these studies are hindered by the legal statuses of both delta-8-THC and delta-9-THC. Cross-sector collaborations among academics, government officials, and representatives from the cannabis industry may accelerate the generation of knowledge regarding delta-8-THC and other cannabinoids. A strength of this study is that it is the first large survey of delta-8 users, limitations include self-report data from a self-selected convenience sample.